Vestibular-evoked myogenic potential triggered by galvanic vestibular stimulation may reveal subclinical alterations in human T-cell lymphotropic virus type 1-associated myelopathy - Labanca, Ludimila (PLoS One, 2018)
BACKGROUND: Vestibular-evoked myogenic potential triggered by galvanic vestibular stimulation (galvanic-VEMP) evaluates the motor spinal cord and identifies subclinical myelopathies. We used galvanic-VEMP to compare spinal cord function in individuals infected with human T-cell lymphotropic virus type 1 (HTLV-1) from asymptomatic status to HTLV-1-associated myelopathy (HAM). METHODOLOGY/PRINCIPAL FINDINGS: This cross-sectional study with 122 individuals included 26 HTLV-1-asymptomatic carriers, 26 individuals with possible HAM, 25 individuals with HAM, and 45 HTLV-1-seronegative individuals (controls). The groups were similar regarding gender, age, and height. Galvanic stimuli (duration: 400 ms; intensity: 2 mA) were applied bilaterally to the mastoid processes and VEMP was recorded from the gastrocnemius muscle. The electromyographic parameters investigated were the latency and amplitude of the short-latency (SL) and medium-latency (ML) responses. While SL and ML amplitudes were similar between groups, SL and ML latencies were delayed in the HTLV-1 groups compared to the control group (p<0.001). Using neurological examination as the gold standard, ROC curve showed an area under the curve of 0.83 (p<0.001) for SL and 0.86 (p<0.001) for ML to detect spinal cord injury. Sensibility and specificity were, respectively, 76% and 86% for SL and 79% and 85% for ML. Galvanic-VEMP disclosed alterations that were progressive in HTLV-1-neurological disease, ranging from SL delayed latency in HTLV-1-asymptomatic carriers, SL and ML delayed latency in possible HAM group, to absence of VEMP response in HAM group. CONCLUSIONS/SIGNIFICANCE: The worse the galvanic-VEMP response, the more severe the myelopathy. Galvanic-VEMP alteration followed a pattern of alteration and may be a prognostic marker of progression from HTLV-1-asymptomatic carrier to HAM.